2022
DOI: 10.1371/journal.pone.0276642
|View full text |Cite
|
Sign up to set email alerts
|

Association between the morphokinetics of in-vitro-derived bovine embryos and the transcriptomic profile of the derived blastocysts

Abstract: The time-lapse system is a non-invasive method that enables a continuous evaluation through embryo development. Here, we examined the association between the morphokinetics of the developing embryo and the transcriptomic profile of the formed blastocysts. Bovine oocytes were matured and fertilized in vitro; then, the putative zygotes were cultured in an incubator equipped with a time-lapse system. Based on the first-cleavage pattern, embryos were categorized as normal or abnormal (68.5±2.2 and 31.6±2.3%, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 90 publications
2
12
0
Order By: Relevance
“…Hence, there seems to be an association between blastomere size, nuclear content, and multipolar division. With regard to abnormal cleavage events, we found lower developmental capacity in zygotes with multipolar cleavage or ruffling membrane, which is in line with human studies 29,37 and recent publications in human and bovine zygotes that showed how multipolar division leads to lower embryo development compared to normal cleavers 30,34 . As supported by the higher number of nuclear abnormalities following multipolar zygotic division, multipolar zygotic division seems to be associated with genome segregation errors in embryos leading to a higher frequency of mixoploidy, and chromosomal abnormalities in the resultant embryos 33,39,41 and embryonic arrest 30 .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Hence, there seems to be an association between blastomere size, nuclear content, and multipolar division. With regard to abnormal cleavage events, we found lower developmental capacity in zygotes with multipolar cleavage or ruffling membrane, which is in line with human studies 29,37 and recent publications in human and bovine zygotes that showed how multipolar division leads to lower embryo development compared to normal cleavers 30,34 . As supported by the higher number of nuclear abnormalities following multipolar zygotic division, multipolar zygotic division seems to be associated with genome segregation errors in embryos leading to a higher frequency of mixoploidy, and chromosomal abnormalities in the resultant embryos 33,39,41 and embryonic arrest 30 .…”
Section: Discussionsupporting
confidence: 91%
“…In our hands, the average time to reach the first division for fresh cumulus enclosed oocytes in serum free culture was slightly higher (33 h) than in other studies (~ 25 h) 33,36,39,41 , which may be related to the use of fetal calf serum in those studies, as this has been demonstrated to accelerate embryo development 59,60 . On the other hand, our results also matched with studies in bovine 34,41 and humans 61 which showed that differences in blastomere size after zygotic division decrease subsequent developmental potential. Our ROC curve results revealed the ideal cut-point for differentiating between even and uneven blastomeres (< 24% difference in area).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations